Sintering behavior and dielectric properties of KCa2Nb3O10 ceramics - Kweon, Sang-Hyo; Im, Mir; Han, Guifang; Kim, Jin-Seong; Nahm, Sahn; Choi, Ji-Won; Hwang, Seong-Ju (ELSEVIER SCI LTD, 2013)
Dense KCa2Nb3O10 (KCN) oxides were synthesized and their dielectric properties were investigated. A homogeneous KCN phase was formed in the specimen sintered above 1300 degrees C, but a CaNb2O6 secondary phase was developed in the specimen sintered at 1400 degrees C, as result of the evaporation of K2O. The KCN oxides sintered at 1375 C showed a high relative density that was 97.1% of the theoretical density. Furthermore, liquid-phase-assisted abnormal grain growth occurred during sintering. The dielectric constant of this KCN oxide was 46, with a low dielectric loss of 0.9% at 100 kHz; these values are smaller than those that were previously reported. Complex impedance analysis indicated that the resistivity of the KCN oxide was very low, probably as a result of the presence of K+ ions between the layers, and this could be the origin of the low-frequency dispersion of the KCN oxides. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: (BA,SR)TIO3 THIN-FILMS; DEPOSITION; OXIDE